Investigating the effect of the satisfaction level of marriage types on the continuity and quality of married life in Iranian society case study: married women in Tehran, districts (1, 2, 6, 8, and 12) - Shafaat , Zahra; Haghighatian , Mansour; Esmaili , Mohammad Reza (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The purpose of the present study was to investigate the effect of the level of satisfaction with different types of marriage on the continuity and quality of married life among married women in Tehran. Methods: The current research is of an applied type, which was done with a questionnaire and a survey method. The statistical population of this study was all married women in Tehran in districts 1, 2, 6, 8, 12, which was calculated as a sample population of 384 people through Cochran’s formula. Bradbury, Fincham and Beach (2000) and Enrich Olson’s Marital Satisfaction Questionnaire (1998) have been obtained. The data analysis was done in two parts, in the first part and model design from PLS software in the second part and hypothesis testing from the regression test was performed with SPSS 22 software. Results: The results showed that the types of marriage have a relationship with the quality of life and its continuity (sig≤0.05), but in the case of forced marriage, this relationship is inverse (sig>0.05). Conclusion: It can be concluded that the way the marriage takes place will affect the fate of a couple’s marriage. Therefore, culture building here is very necessary to prevent forced marriages at very young ages and also to eliminate the norms and subcultures that hinder marriage and family formation.